Balinese perspective in Myths and Diseases: How the society copes and survive the situation - Yogi Meranggi (Bali Tourism Board, 2020)
Myths are common in Balinese society’ belief system that rooted back to the local religion, Wali and Hinduism teaching. There are many stories in ancient texts; most of them cover the story of influential figures such as Gods, Deities, Demon, evil spirit and et cetera. Gods and Goddess represent good, righteousness and source that brings happiness and joy to human. In contrast, other entities like Demons and evil spirits become a symbol of maleficent that create chaos and disaster on earth. Through Balinese history, there were many disasters, plagues, and diseases that took heavy tolls. The Myth from ancient Balinese texts helps to provide consultation as well as the perspective of the ancient civilisation in dealing with many unfortunate situations, including plagues and diseases. The mythical story leads to numerous ceremonies being celebrated on the island. The ritual act as an expression of gratitude, apologise, and a moment to self-reflect that humankind is not the only creature that inhabits the universe. The teaching emphasises that the local community is mandatory to take care of their environment, avoid exploiting nature, subsequently as an alarm to the individual to live in humble and responsible. Despite the locals are well adapted to modern technology and received higher education, apparently did not halt the rites. They believed the activities are identity as well as precious treasure from their honourable ancestor.